RISK FACTORS AND INTERVENTION MEASURES FOR POSTURAL CHANGES AND THE IMPACT ON QUALITY OF LIFE: A LITERATURE REVIEW - Araujo, Lucele Gonçalves Lima; Oliveira, Guilherme José Pimentel Lopes de; Rodrigues, Vandilson Pinheiro (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
Objective: This study investigated risk factors and the impact of intervention measures for postural alterations on quality of life. A literature review was conducted to answer the guiding problem of this study: what are the risk factors for postural alterations and the impact of interventions on quality of life? Materials and methods: The search procedure was carried out in the following databases: MedLine via PubMed, Scopus, Web of Science, Cochrane Library, Embase and Lilacs. Of the 527 articles initially found, 14 met the eligibility criteria for this study. Results: Seven articles were identified which investigated risk factors associated with postural alterations, such as: musculoskeletal symptoms, pregnancy, overweight and obesity, inadequate sitting posture, axial spondyloarthritis, smoking, low back pain and neck pain. Seven articles evaluated interventions used to improve the quality of life of patients with postural alterations, including: lumbar mobility and stretching exercises + unilateral PA mobilization + hot compress, Schroth exercises, RPG ('frog on the floor' posture) / cranio-cervical flexion test, McKenzie approach and spinal stabilization exercises, evidence-based physiotherapy treatment and thoracic muscle strengthening exercises. Conclusions: The findings indicate that postural alterations have a multifactorial etiology and that clinical interventions can be effective. It is suggested that research be carried out into the early identification of risk factors and interventions tailored to the needs of each patient to promote health and improve quality of life.